Organizational sources of stress in primary school teacher and their relacionship to the number of pupils taught - Madrigal Olivas, Guadalupe; Barraza Macías, Arturo (Avances en Supervisión Educativa, 2014)
The objectives of this research are: Identify sources of organizational stressors on teachers and establish the relationship between the level of organizational stress and the number of students attending teachers. To achieve these objectives, a non-experimental, cross-sectional correlational study was conducted through the application of the Organizational Sources of Stress Teachers Scale (EFOED) to 59 teachers of School District No. 5 of the Ministry of State Education Durango, Mexico. Their main results suggest that uncertainty by the new educational reforms and their impact on labor rights is a situation that creates instability in the educational work of teachers, coupled with this lack of information on it and the constant rumors that generated around it.
Keywords: stress; organization; school; teachers